1996
DOI: 10.18388/abp.1996_4580
|View full text |Cite
|
Sign up to set email alerts
|

Human lipoprotein lipase deficiency: does chronic dyslipidemia lead to increased oxidative stress and mitochondrial DNA damage in blood cells?

Abstract: Lipoprotein lipase (LPL) is a key enzyme in the metabolism of lipoproteins and their balanced distribution in the plasma. A deficiency of this enzyme due to gene mutations leads to severe dyslipidemia. In this report, we describe the major LPL gene mutations that are prevalent in the French-Canadian population of Québec and the nature of dyslipidemia caused by the resulting enzyme deficiency. We discuss the possibility that dyslipidemia caused by LPL deficiency may enhance oxidative stress in the blood cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…It can be highlighted that the mechanism of action of Nicarbazin and its ingredients in alternation of oxidative stress level may have different pathway because there are lots of structures proposed but none is precisely approved. As it said NCZ can increase the action of some enzymes in the metabolism of body, like lipoprotein lipase 8 , and variation in the activity of these enzymes can consequently impress the antioxidative defense system [15][16][17][18][19][20][21][22] . In conclusion lipoprotein lipase activation may be the most effective pathway in calling Nicarbazin as sources for oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be highlighted that the mechanism of action of Nicarbazin and its ingredients in alternation of oxidative stress level may have different pathway because there are lots of structures proposed but none is precisely approved. As it said NCZ can increase the action of some enzymes in the metabolism of body, like lipoprotein lipase 8 , and variation in the activity of these enzymes can consequently impress the antioxidative defense system [15][16][17][18][19][20][21][22] . In conclusion lipoprotein lipase activation may be the most effective pathway in calling Nicarbazin as sources for oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, by the best of literature review, no evidence was found which can illustrate the long term effects of this drug. But if we consider that NCZ can activate lipoprotein lipase 8 , and take into account the relationships between lipoprotein lipase expression and oxidative stress, concluded from different studies [15][16][17][18][19][20][21][22] , it may hypothesized that Nicarbazin can affect the oxidative situation of cells.…”
mentioning
confidence: 99%
“…Due to the high morbidity and mortality in these patients, the prevention of cardiovascular complications has become a primary objective in the management of diabetes [ 7 ]. In addition to insulin resistance, other cardiovascular risk factors include dyslipidemia, hypertension, susceptibility to coagulation, obesity, hyperinsulinemia and inflammation [ 8 , 9 ]. Dyslipidemia, one of the most important risk factors, includes various pathologic conditions involving abnormal concentration, composition and distribution of lipids.…”
Section: Introductionmentioning
confidence: 99%